Influence of chlorine added to drinking water during the preslaughter feed withdrawal on microbiology and morphology of the broiler gastrointestinal tract - Barreiro, F. R. [UNESP]; Baraldi-Artoni, Silvana Martinez [UNESP]; Pinto, F. R. [UNESP]; Barbosa, M. M. C. [UNESP]; Barbosa, J. C. [UNESP]; Amaral, L. A. [UNESP] (Poultry Science Assoc Inc, 2012)
The objective of this experiment was to test the effects of the addition of chlorine to broiler drinking water during a 12-h preslaughter feed withdrawal period on reduction of the quantities of microorganisms, such as Escherichia coli and enterococci, in broiler crops and ceca. Reduction of these microorganisms would likely also reduce contamination of broiler meat by pathogenic bacteria during processing. It was also investigated if the chlorine caused some intestinal damage that could disseminate the microorganisms to the carcass. A total of 40 Cobb male broilers were used. Samples of crop and cecal content were collected for microbiological analysis, and duodenum and jejunum were used for morphological analysis from 10 birds in each treatment. The most probable number (MPN) of E. coli and enterococci in the collected samples of crop and ceca and the measure of the free residual chlorine in water were determined. The scanning electron microscopy from duodenum and jejunum was used to illustrate the mucosa integrity. The chlorine added to water was efficient in reducing the quantities of microorganisms in broiler crops and improved the integrity of the mucosa. Therefore, preslaughter feed withdrawal should be coupled with crop disinfection, because preslaughter feed withdrawal increases the MPN of enterococci and E. coli in broiler crops. So, it presents a higher risk for carcass contamination during slaughterhouse processing and, consequently, a higher risk for public health.
Keywords: Chlorine; enterococci; Escherichia coli; Microscopy; preslaughter feed withdrawal